Cardiac sarcoidosis masquerading as arrhythmogenic right ventricular cardiomyopathy: a case report. Issue 3 (13th March 2021) - Pendela, Venkata Satish; Kudaravalli, Pujitha; Feitell, Scott; Parikh, Vishal
Abstract: Background: Cardiac sarcoidosis (CS) and arrhythmogenic right ventricular cardiomyopathy (ARVC) are rare causes of ventricular arrhythmias and are associated with sudden cardiac death. Differentiation between both is important for proper management. Case summary: We present a 56-year-old man with sudden cardiac arrest and was diagnosed to have ARVC based on cardiac magnetic resonance imaging (MRI). He developed gradually worsening shortness of breath over the next 1 year. CS was unmasked after a cardiac positron emission tomography (PET). Patient was treated with methotrexate. A repeat cardiac PET scan showed improvement. Discussion: The distinction between ARVC and CS is challenging. Both these entities have a patchy involvement and can have similar presentations. ARVC has a predominant right heart involvement. It is diagnosed with the help of an MRI, which shows regional right ventricular wall motion abnormality. These findings can have an overlap with CS. It is important to note that, even though sarcoidosis is a pathologic diagnosis, cardiac biopsy is rarely done owing to its patchy involvement. Cardiac PET scan has a high sensitivity and specificity to diagnose this entity. Once diagnosis is made, patients should be treated with immunosuppressants and should be closely followed. Repeat imaging should be considered at intervals to monitor disease progression. This case highlights the importance of multimodality imaging and tissue diagnosis to unmask the diagnosis of CS, a treatable infiltrative disorder which shares features with a potentially untreatable ARVC.